The role of bone scan in the diagnosis of Jaffé-Lichtenstein-Uehlinger syndrome - Chroustova, Daniela; Votruba, Michal; Sprindrich, Jan; Sosna, Bohuslav (Nuclear medicine review. Central & Eastern Europe, 2004)
The case of a 12-year-old girl with Jaffé-Lichtenstein-Uehlinger syndrome is presented. A bone scan pattern exhibits clinical symptoms, X ray images and histological findings are described in a case of polyostotic form of the fibrous dysplasia. A biopsy with histology was performed in consideration of bone scan findings and a confirmed final diagnosis.
Keywords: Bone Neoplasms; radioisotopová scintigrafie; Technetium Tc 99m Medronate; lidé; Humans; Child; radiofarmaka; Radionuclide Imaging; Fibrous Dysplasia of Bone; syndrom; fibrózní dysplazie kosti; technecium 99mTc medronát; Whole-Body Counting; celotělové počítání; kosti a kostní tkáň; Bone and Bones; Radiopharmaceuticals; nádory kostí; dítě; ženské pohlaví; Female; Syndrome